Two new plant feeding mites from Brachiaria ruziziensis in citrus groves in S o Paulo, Brazil and new distribution records of other plant mites in Brazil - Flechtmann, Carlos H.w. (Zootaxa, 2004)
Two new species of phytophagous mites are described from Brachiaria ruziziensis (Poaceae), namely Catarhinus brachiariae n.sp. belonging to the Diptilomiopidae, and Eotetranychus herbicolus n.sp. a member of the Tetranychidae. New distribution records of other plant feeding mites in Brazil are also presented.